Night eating syndrome – characterization - Olejniczak, Dominik; Skonieczna, Joanna; Kitowska, Wioleta (Journal of Education, Health and Sport, 2018)
The definition of the Polish National Food and Nutrition Institute indicates that proper human nutrition should completely satisfy the body's needs for energy as well as provide all nutrients needed for the development of life and preservation of health. This article is devoted to the relatively recently described issue, pertaining to eating disorders, that is night eating syndrome (NES). Nowadays, food has become a tool used for improving one’s well-being, which has contributed to an increase in the frequency of eating disorders and lifestyle diseases such as obesity. Night eating syndrome is important in the pathogenesis of obesity and for this reason, in the near future, it may become an important problem in public health. Night eating syndrome can be a difficult disorder to diagnose. Identification may be hindered by the lack of a unified definition, lack of coherent diagnostic criteria or diagnostic method, and problems with classification, which contributes to difficulties in fully understanding the disorder.